Making scenes : global perspectives on scenes in rock art - Davidson, Iain, 1948-; Nowell, April, 1969- (Berghahn Books, 2021)
"Dating back to at least 50,000 years ago, rock art is one of the oldest forms of human symbolic expression. Geographically, it spans all the continents on Earth. Scenes are common in some rock art, and recent work suggests that there are some hints of expression that looks like some of the conventions of western scenic art. In this unique volume examining the nature of scenes in rock art, researchers examine what defines a scene, what are the necessary elements of a scene, and what can the evolutionary history tell us about storytelling, sequential memory and cognitive evolution among ancient and living cultures?"--